Gdynia : Kongres Eucharystyczny i Dni Morza 1939 - Durczykiewicz, Leonard (1876-1934). (Gdynia : L. Durczykiewicz, 1939)
Karta pocztowa z uczestnikami Kongresu.
Keywords: Gdynia (Polska) -- 1900-1945 -- karty pocztowe; Karty pocztowe -- 1900-1945.